Genomic and phenotypic analyses reveal Paenibacillus polymyxa PJH16 is a potential biocontrol agent against cucumber fusarium wilt - Yang, Fan; Jiang, Huayan; Ma, Kai; Hegazy, Abeer; Wang, Xin; Liang, Shen; Chang, Gaozheng; Yu, Liqin; Tian, Baoming; Shi, Xuanjie (Frontiers in Microbiology, 2024)
In recent years, bacterial-based biocontrol agents (BCA) have become a new trend for the control of fungal diseases such as fusarium wilt that seriously threaten the yield and quality of cucumber, which are transmitted through infested soil and water. This study was set out with the aim of figuring the mechanism of the isolated rhizobacterial strain Paenibacillus polymyxa PJH16 in preventing Fusarium oxysporum f. sp. cucumerinum (Foc). Biocontrol and growth-promoting experiments revealed that bacterial strain causes effective inhibition of the fungal disease through a significant growth-promoting ability of plants, and had activities of β-1,3-glucanase, cellulase, amylase and protease. It could produce siderophore and indole-3-acetic acid, too. Using the high-throughput sequencing tool PacBio Sequel II system and the database annotation, the bacterial strain was identified as P. polymyxa PJH16 and contained genes encoding for presence of biofilm formation, antimicrobial peptides, siderophores and hydrolyases. From comparing data between the whole genome of P. polymyxa PJH16 with four closely related P. polymyxa strains, findings revealed markedly the subtle differences in their genome sequences and proposed new antifungal substances present in P. polymyxa PJH16. Therefore, P. polymyxa PJH16 could be utilised in bioengineering a microbial formulation for application as biocontrol agent and biostimulant, in the future.